2008
DOI: 10.1001/archderm.144.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Family History as a Risk Factor for Herpes Zoster

Abstract: To assess risk factors for herpes zoster beyond age and immunosuppression, especially the association with a family history of herpes zoster, since a preventative herpes zoster and postherpetic neuralgia vaccine is now available. Design:We undertook a case-control study of herpes zoster, which represents reactivation of latent varicella zoster virus residing in dorsal root ganglia following primary infection, involving 504 patients and 523 controls. Interviews were conducted by trained medical investigators us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 26 publications
4
56
5
Order By: Relevance
“…It should be noted that the population sample examined by Hicks et al [2008] was significantly younger (36.3% of the patients and 31.8% of the controls were over 65 years of age) than that examined in the present study, where more than 80% of the patients and the controls were over 65 years of age. It is known that the lifetime risk of developing herpes zoster is about 20-30%.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…It should be noted that the population sample examined by Hicks et al [2008] was significantly younger (36.3% of the patients and 31.8% of the controls were over 65 years of age) than that examined in the present study, where more than 80% of the patients and the controls were over 65 years of age. It is known that the lifetime risk of developing herpes zoster is about 20-30%.…”
Section: Discussioncontrasting
confidence: 63%
“…It is noted that whereas the percentages of the patients who reported a family history of zoster were relatively similar in the two studies (i.e., 28.4% in the present study vs. 39.3% reported by Hicks et al [2008]), a percentage of controls with a positive family history of zoster much higher than that found by Hicks et al [2008] was found in the present study (i.e., 29.6% vs. 10.5%, respectively). It is difficult to speculate on the possible reasons for the discrepancy of the two studies, but some possible conclusions may be drawn.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations